Результаты дистанционных и наземных геоэлектрических исследований на участках расположения хранилищ нефтепродуктов - Левашов, С.П.; Зезекало, И.Г.; Якимчук, Н.А.; Корчагин, И.Н.; Божежа, Д.Н. (Геоінформатика, 2016)
Анализируются результаты исследований с использованием мобильных прямопоисковых методов на территориях подземного и наземного хранилищ нефтепродуктов. На первом этапе обследования подземного хранилища дизельного топлива выполнена частотно-резонансная обработка спутникового снимка участка его расположения. На втором этапе на площади хранилища проведены наземные детализационные работы геоэлектрическими методами СКИП и ВЭРЗ. В результате обнаружены и закартированы остатки дизельного топлива в двух подземных емкостях (резервуарах) в объемах 5621 и 243 м³. В зонах других емкостей остатки нефтепродуктов не выявлены. На участке работ установлен и локализован вертикальный канал миграции глубинных флюидов, по которому газ и “легкая нефть” нагнетаются по тектоническим нарушениям на территорию хранилища. На площади наземного хранилища обнаружено и закартировано 12 аномальных зон на резонансных частотах проб топлива из пробуренных скважин. В контурах аномальных зон по значениям интенсивности аномального отклика выделены наиболее перспективные участки для бурения скважин с целью извлечения «утерянного» топлива. Наличие техногенных скоплений топлива в контурах выявленных аномальных зон подтверждено бурением. Проаналізовано результати досліджень з використанням мобільних прямопошукових методів на територіях підземного і наземного сховищ нафтопродуктів. На першому етапі обстеження підземного сховища дизельного палива виконано частотно-резонансну обробку супутникового знімка ділянки його розташування. На другому етапі на площі сховища проведено наземні деталізаційні роботи геоелектричними методами СКІП і ВЕРЗ. У результаті виявлено та закартовано залишки дизельного палива у двох підземних резервуарах об’ємом 5621 і 243 м³ . У зонах інших резервуарів залишки нафтопродуктів не виявлено. На ділянці робіт установлено і локалізовано вертикальний канал міграції глибинних флюїдів, по якому газ і “легка нафта” нагнітаються по тектонічних порушеннях на територію сховища. На площі наземного сховища виявлено та закартовано 12 аномальних зон на резонансних частотах проб палива із пробурених свердловин. У контурах аномальних зон за значеннями інтенсивності аномального відгуку виділено найперспективніші ділянки для буріння свердловин з метою вилучення “втраченого” палива. Наявність техногенних скупчень палива в контурах виявлених аномальних зон підтверджено бурінням. Purpose of the paper is to study the possibility of the mobile direct-prospecting methods using for exploration and delineation of “man-made” fuel accumulations on the underground and ground petroleum storage facilities; to search and localize the vertical channel of deep fluids migration; to improve the methodological application principles of direct-prospecting geophysical methods and techniques for solving the problems of near-surface geophysics. Design/methodology/approach. The experiments were carried out using a mobile direct-prospecting technology that includes the method of frequency-resonance processing of satellite images and ground-based geoelectric methods FSPEF and VERS. Particular methods of this technology are based on the principles of a “substance” paradigm of geophysical studies and provide the ability to detect and map operatively the anomalous zones of the “hydrocarbons deposit (oil, gas and gas condensate)” type. Within the contours of detected the anomalous zones the maximum values of fluid pressure in the reservoirs are estimated by the resonant frequencies of gas at different intervals of the cross-section. Findings. At the first stage of the survey of the underground storage of diesel fuel we carried out frequency-resonance processing of satellite images of its location area. At the second stage we conducted the detailed ground-based works within the storage area, using the geoelectric FSPEF and VERS methods. As a result, the diesel residues of 5621.0 m³ and 243.0 m³ volume were detected and mapped in two underground tanks. In the areas of other tanks the oil residues were not detected. Within the working area, vertical channel of deep fluids migration was detected and localized, by which gas and “light oil are pumped through the tectonic fractures into the storage territory. At the surveyed area of ground storage, 12 anomalous zones were detected and mapped at the resonant frequencies of fuel samples from drilled wells. Within the contours of the detected anomalous zones, the most prospective areas for drilling wells to extract the “lost fuel” were identified by the values of the anomalous response intensity. The presence of man-made fuel accumulations in the contours of the detected anomalous zones was confirmed by drilling. The practical significance and conclusions. Studies have demonstrated the high efficacy of individual methods of direct-prospecting geophysical technology for exploration and delineation of “man-made” petroleum accumulations. Frequency-resonance processing of satellite images and area survey by FSPEF method allows us to highlight and map areas of oil accumulation, zones of underground water flows migration and high humidity of soil. Methods of images vertical scanning and of VERS sounding permit to determine the depth to the “man-made (lost)” petroleum products, wetlands, underwater streams, boundaries between different rock complexes, suffusion cavities, sinkholes and valleys. This complex of methods will allow us to carry out laboratory research and make field geophysical mea-surements quickly and in a short period of time, which leads to a significant reduction in the timing of the work of environmental engineering and surveying character.